Catalytically propelled 3D printed colloidal microswimmers. Issue 46 (15th October 2020) - Doherty, Rachel P.; Varkevisser, Thijs; Teunisse, Margot; Hoecht, Jonas; Ketzetzi, Stefania; Ouhajji, Samia; Kraft, Daniela J.
Abstract : 3D microprinting allows the preparation of colloidal microswimmers with unlimited shape complexity furthering the understanding of out-of-equilibrium phenomenon. Abstract : Synthetic microswimmers are widely employed model systems in the studies of out-of-equilibrium phenomena. Unlike biological microswimmers which naturally occur in various shapes and forms, synthetic microswimmers have so far been limited almost exclusively to spherical shapes. Here, we exploit 3D printing to produce microswimmers with complex shapes in the colloidal size regime. We establish the flexibility of 3D printing by two-photon polymerisation to produce particles smaller than 10 microns with a high-degree of shape complexity. We further demonstrate that 3D printing allows control over the location of the active site through orienting the particles in different directions during printing. We verify that particles behave colloidally by imaging their motion in the passive and active states and by investigating their mean square displacement. In addition, we find that particles exhibit shape-dependant behavior, thereby demonstrating the potential of our method to launch a wide-range of in-depth studies into shape-dependent active motion and behaviour.